A propose framework of smart parking system (SPS) / Wan Mohd Hisham Wan Hamzah - Wan Hamzah, Wan Mohd Hisham (Faculty of Information Technology and Quantitative Sciences, 2005)
With the increase number of cars, there is a high demand in parking space but low supply in available parking space. With the limited amount of resources especially land; it is important to organize the resources in an efficient way. So researcher has come out with a research to identify the problem regarding parking space system especially at parking garage and at the mean time to propose a fi-amework for new system for the parking system called Smart Parking System (SPS). In analyzing the problem regarding parking space system, researcher has done the study by using research model that contains several variables. The sample of the study is parking garage user at Klang Valley area. A total of 120 samples of parking space user were chosen around Klang Valley. A couple of test is carried on the variables that are important in order to obtain the intention results required by the objective that have been stated in the early stage of the research. The analysis indicates that the parking system need to be improved in certain area and will be discussed later. Based on the analysis and finding. Researcher has designed the fimnework for the Smart Parking System (SPS). Researcher has used Unified Modeling Language (UML) as a tool to designing the system and the requirement is depend on the analysis that has been made earlier. Unified Modeling Language (UML) will help in designing the analysis model to build up final artifact of requirement development process that knows as Software Requirement Specification (SRS). By proposed a fi"amework of Smart Parking System (SPS), it can transform the traditional parking system to the electronic parking system that more user fiiendly. The design of the system is still can be improved with fixture research and study.